Classification and Selection of Edible Cassava Lines Based on Cyanide Levels - Ashok, P; George, James; Priyanka, A Pavani (JOURNAL OF ROOT CROPS, 2017)
Cassava contains naturally occurring, but potentially toxic compounds called cyanogenic glycosides, which release hydrogen cyanide (HCN) as a result of enzymatic hydrolysis following maceration of the plant tissue. The consumption of cassava can therefore be harmful to human health. Cassava and its products have drawn attention by international food safety regulators on a number of occasions. Although varieties are selected for their agronomic characteristics, their low levels of cyanide classify them for culinary use; those with higher levels are selected for industrial use. Hence an experiment was conducted to classify the 75 genotypes of cassava based on the cyanide levels. Sodium picrate method was used to determine the cyanide levels. Seventy five genotypes of Cassava were classified into low (0 to 50 ppm), medium (50-100ppm) and high (more than 100 ppm) cyanide groups. Twenty one edible genotypes showed a variation of potential cyanide between 24.3 ppm to 48.7 ppm classifying them as harmless. The accession MeAp-1 recorded highest cyanide content of 256.1 ppm which is fit for industrial use. The genotypes classified under low cyanide levels were for further evaluated for reducing sugars, non reducing sugars, starch and other agronomical characters to identify the best edible genotypes. The results revealed that Me AP-72 (PA-46) genotype registered highest values for reducing sugars (6.5%), non reducing sugars (5.2%), total sugars (11.7%) and least values for HCN content (24.3 ppm) and starch (17 %).